MISOPROSTOL VS OXYTOCIN ON INDUCTION OF LABOR IN PREMATURE RUPTURE OF MEMBRANES - Raygada, José (2015)
OBJETIVE: To evaluate the characteristics and complications of induced labor with intravaginal misoprostol versus intravenous oxytocin in pregnant women at term with premature rupture of membranes (PROM) without evidence of spontaneous labor. DESIGN: Retrospective, descriptive and comparative study. LOCATION: Department of Obstetrics of Loayza Hospital. MATERAIL AND METHODS: The medical records of 92 pregnant women at term with RPM was reviewed under conditions to be induced. The effects of intravenous oxytocin in 49 patients (group 1], according to protocol, versus intravaginal misoprostol in 43 patients (Group 2), or 50 mg every 4 hours was assessed to achieve adequate uterine contractions or reach 300 mg RESULTS.: The induction was more successful in the misoprostol group (74.4%) compared to oxytocin (61.2%), but without statistical significance (p = 0.18). The interval from the start of induction to delivery was significantly lower in multiparous and use of oxytocin (426.1 ± 208.4 min) than with misoprostol (621.9 ± 267.7) (p <0.001). No significant difference in the type of delivery, signs fetal distress, dystocia funicular and other complications in childbirth and postpartum. CONCLUSIONS: The intravaginal misoprostol is an effective alternative in the induction of labor in pregnant women at term with RPM, in our study did not increase the cesarean rate and maternal and neonatal complications were similar.